Pengaruh Tata Kelola terhadap Kesulitan Keuangan dengan Moderasi Reputasi Perusahaan - Chandra, Budi; Santikawati; Ivone (Universitas Sarjanawiyata Tamansiswa, 2024)
The aim of this research is to examine the impact of corporate governance on financial difficulties seen in companies listed on the Indonesia Stock Exchange. The data analysis technique used in this research involves the use of panel regression. The software used for testing purposes is Eviews. This research aims to conduct an analysis of manufacturing companies listed on the Indonesia Stock Exchange throughout the period 2018 to 2021. The research results are interpreted to mean that financial difficulties are influenced by family ownership and institutional ownership. In contrast, financial difficulties are not influenced by managerial ownership and board size. Furthermore, other research results include financial difficulties that are not influenced by family ownership, institutional ownership, managerial ownership, and board size with the company's reputation as a moderator.